A comparative anion diffusion study on different argillaceous, low permeability sedimentary rocks with various pore waters. (May 2018) - Wigger, Cornelia; Kennell-Morrison, Laura; Jensen, Mark; Glaus, Martin; Van Loon, Luc
Abstract: Through-diffusion experiments with tritiated water (HTO) and 36 Cl − as a function of pore water concentration (0.01–5 M) were performed on two Ordovician-age argillaceous rock samples from the Blue Mountain Fm and Queenston Fm shales of the Paleozoic intracratonic Michigan Basin in Canada. This study reveals that the effect of ionic strength on the anion-transport porosity is similar, and only the minimal anion excluded porosity is higher in the Blue Mountain Fm shale. The differences in rock sample mineralogy cannot explain this effect. It is hypothesized that the structure of the Blue Mountain Fm shale samples has led to pore space openings sufficiently small that they behave as interlayers. Such pores are defined as interlayer equivalent (ILE) pores. These ILE pores, as in the case of interlayer pores, can act to permanently limit the anion-accessible porosity. Pore-size distribution measurements provide further evidence of increased potential for ILE pores within the Blue Mountain Fm samples. A Donnan model, which includes consideration of both ILE and uncharged pores, is shown to describe the effect of molar concentration on the anion-accessible porosity in the argillaceous rocks investigated. Highlights: The anion porosity increases with increasing molar pore water concentration. The total porosity is independent of the pore water compositions. Total porosity values determined by HTO-diffusion are equal to H2 O-loss porosity. PSD measurements indicate more ILE pores present in the BM Fm than in the Q Fm.